Edukasi Bahaya Kekerasan Verbal (Bullyying) Bagi Siswa SD Negeri 1 Rumahtiga - Eva Susan Ratuluhain; Ronald Darlly Hukubun; Stefanno M. A. Rijoly; Salma Rumau; Suryani Makassar; Siti Rukmana Wally; Alessandra F. Saija; Ivanmorl Ruspanah (Politeknik Kampar, 2024)
Bullying is an act of physical or verbal violence that is carried out intentionally and repeatedly, with the aim of causing psychological suffering to the victim. Bullying is a serious problem, which is currently widespread at both local and international levels and can occur directly or online. The current case of bullying that is of particular concern is in the school environment. An example of a case that occurred was an 11-year-old student at an elementary school in Banyuwangi, who was found dead by hanging himself as a result of being frequently bullied at his school. This is the background to the importance of early education for elementary school students. Based on this, the 2023/2024 batch L of Pattimura Unvesitas KKN students carried out an educational program through counseling methods about education and the impact of bullying on children's health, mental and emotional health. This program was implemented for 30 students of SD Negeri 1 Rumah Tiga. The delivery of the counseling material was carried out in 3 sessions, namely a material presentation session, a question and answer session, and a group photo session. The results of the activity can be concluded that at first the students did not understand what bullying was, but after presenting material about what bullying is and how it impacts children's mental and emotional health, the students were very enthusiastic and immediately understood the material presented.